Students' Perceived Use of MyELT in English Language Learning: Attitude, Perceived Knowledge, and Perceived Benefit - Zuraina, Ali; Kalarikkal, Firos; Rosnani, Ismail; Khenfer, Madjida Oumayma (Universiti Teknologi Malaysia, 2021)
The use of technology is paramount in learning. Its uses enable language learners to learn the language as a second or foreign language. The current study investigates the use of MyELT, a web-based learning management system, to assist students in learning English. Specifically, it examines the relationship between students' perceived benefits and perceived knowledge of using MyELT with their attitudes. Also, it gauges the significant differences between male and female students in their attitude, perceived benefits, and perceived knowledge. The study found positive correlations between students' perceived benefits and perceived knowledge with their attitudes of using MyELT. Regarding gender differences in using MyELT, there was not enough evidence to show that there were statistical differences using the resource in their attitudes, perceived benefits, and perceived knowledge. The study implied that using MyELT can promote a positive attitude, perceived knowledge, and perceived benefits of learning English. Yet, evidence was still not sufficient to prove a significant difference in gender in the tested variables.